Blue Lives Matter and Hate Crime Law. (April 2022) - Mason, Gail
The Blue Lives Matter movement began in 2014 as a rejoinder to accusations of police racism in the United States. Blue Lives Matter advocates for the expansion of hate crime statutes to include police and other first responders as protected victim categories. Four US states have enacted such reforms: Louisiana, Kentucky, Mississippi and Texas. With some minor exceptions, this is the first time that hate crime laws have been extended to a victim category that represents an authoritative arm of the state. This article examines the social significance of these laws. Drawing on the results of a critical discourse analysis of legislative debates surrounding the enactment and attempted enactment of blue hate crime laws, the article argues that these laws pit police and Black citizens against each other. In situating new legal protections for police within hate crime statutes, blue reforms contain an implicit attempt to reframe the history of police brutality toward Black Americans by claiming that police are a subjugated and targeted minority at the hands of a Black community of dangerous and biased perpetrators: a new black/blue relation of power.